SOCIAL MEDIA & YOUTH: IDENTIFYING IMPACT MEDIA SOCIAL CONCERNS FOR ADOLESCENT LANGUAGE DEVELOPMENT - Naila Salsabila Munigar; Devi Yanti; Muhammad Riza Ananta Andriana; Khalila Ainul Fathiyah; Regina Anorra (Study Program Guidance and Counseling, Univesitas Pendidik, 2024)
Digital technology is developing very rapidly in the current era of globalization, one of which is visibleon social media popularity. Teenagers are the subjects most vulnerable to the development of social media. According to a report from the Ministry of Communication and Information, around 79.5% of children and teenagers are internet users, and almost98% of them have knowledge about the internet. Therefore, discussions about social media on adolescent language development need to be of concern to various groups. This research uses a literature study method through searching and analyzing various sources of information, including scientific journals, books, reports and relevant documents as well as processing research language. Media developmentsSocial media has a significant impact on language development in adolescents. Resultsresearch shows that social media has a profound impact onlanguage development in adolescents